Transformation of Religious Fundamentals for Students in Religious Studies at Balai Pengajian Guru Sekumpul, Pidie Regency - Saputra, Nanda (Teumulong: Journal of Community Service, 2023)
Religious diversity is one of the significant aspects of Indonesian society. Among the various religions practiced in Indonesia, Islam has the largest number of followers. In this context, Islamic boarding schools or "pondok pesantren" and religious madrasas play a crucial role in strengthening the fundamental understanding of religion for the young Islamic generation, commonly known as "santri." One of the Islamic boarding schools that actively contributes to the development of religious knowledge among santri is BP Guru Sekumpul, located in Pidie Regency, Aceh. In this article on Community Service, I will discuss the community engagement activities conducted at BP Guru Sekumpul in Pidie Regency, Aceh, which aim to deepen the basic understanding of religion among santri in Aceh Pidie.